Ocular Sarcoidosis - Sève, Pascal; Jamilloux, Yvan; Tilikete, Caroline; Gerfaud-Valentin, Mathieu; Kodjikian, Laurent; El Jammal, Thomas (Seminars in Respiratory and Critical Care Medicine, 2020)
Sarcoidosis is one of the leading causes of inflammatory eye disease. Any part of the eye and its adnexal tissues can be involved. Uveitis and optic neuropathy are the main manifestations, which may require systemic treatment. Two groups of patients with sarcoid uveitis can be distinguished: one of either sex and any ethnicity in which ophthalmological findings are various and another group of elderly Caucasian women with mostly chronic posterior uveitis. Clinically isolated uveitis revealing sarcoidosis remains a strictly ocular condition in a large majority of cases. Although it can be a serious condition involving functional prognosis, early recognition in addition to a growing therapeutic arsenal (including intravitreal implant) has improved the visual prognosis of the disease in recent years. Systemic corticosteroids are indicated when uveitis does not respond to topical corticosteroids or when there is bilateral posterior involvement, especially macular edema. In up to 30% of the cases that require an unacceptable dosage of corticosteroids to maintain remission, additional immunosuppression is used, especially methotrexate. As with other forms of severe noninfectious uveitis, monoclonal antibodies against tumor necrosis factor-α have been used. However, only very rarely does sarcoid uveitis fail to respond to combined corticosteroids and methotrexate therapy, a situation that should suggest either poor adherence or another granulomatous disease. Optic neuropathy often affects women of African and Caribbean origins. Some authors recommend that patients should be treated with high-dose of corticosteroids and concurrent immunosuppression from the onset of this manifestation, which is associated with a poorer outcome.
Keywords: sarcoidosis; uveitis; ocular sarcoidosis; 18-FDG PET; anti-TNF-α